Practice of Universal Infection Control Protocols (Medical Forum Monthly, 2024)
Objective: The objective of this study was to evaluate practice of universal infection control protocols among third and final year BDS students at different dental colleges.Study Design: Comparative studyPlace and Duration of Study: This study was conducted in five dental colleges and hospitals which are affiliated with University of Karachi during the year 2011-2012.Materials and Methods: The undergraduates (third and final professional BDS students were selected with the age range from 18-22 years and without gender discrimination in the year 2011-2012. A self applied, confidential 14 close-ended type questionnaire consisting of various aspects of infection control practice was distributed to these undergraduates at the end of second semester after the lecture with permission and consent of head of institution. The collected data was analyzed by using SPPS 16.0.Results: Among 180 students, 90(50%) were final year students and 90(50%) were third year students. Out of them 70 final year and 72 third year students participated. Thus a total of 142 (77.77%) students completed questionnaire with a response rate of 79%. The final year students were found to have more knowledge and had practiced more infection control procedures than third year students.Conclusion: Compliance with recommended guidelines for cross infection control varies among final year and third year students. Efforts are needed to improve attitudes to implement information and motivate students in the correct and routine use of infection control measures before they commence their clinical rotations.